2013
DOI: 10.4103/0253-7176.116243
|View full text |Cite
|
Sign up to set email alerts
|

Growing Up with a Parent having Schizophrenia: Experiences and Resilience in the Offsprings

Abstract: Background:Parental mental illness has been found to have an impact on offsprings in their emotional, social, and behavioral aspects of life.Aims:To examine the experiences of offsprings of a parent having schizophrenia and to study their resilience.Materials and Methods:A sample of 45 adults with one parent diagnosed with schizophrenia was selected using purposive sampling. Subjects were assessed using socio-demographic data sheet, semi-structured interview schedule, and Connor–Davidson Resilience Scale.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 37 publications
1
16
0
9
Order By: Relevance
“…Stewart and Sun () found that supporting parents at home could have significant effect on students’ resilience. Similarly, Herbert, Manjula, and Philip () showed that experiencing a supportive relationship with parents could increase one's resilience, and Bowes, Maughan, Caspi, Moffitt, and Arseneault () also provided evidence for supporting the positive association between parents’ relationship and resilience. However, there was some research that did not show such positive relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Stewart and Sun () found that supporting parents at home could have significant effect on students’ resilience. Similarly, Herbert, Manjula, and Philip () showed that experiencing a supportive relationship with parents could increase one's resilience, and Bowes, Maughan, Caspi, Moffitt, and Arseneault () also provided evidence for supporting the positive association between parents’ relationship and resilience. However, there was some research that did not show such positive relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Girls had higher rate of emotional problems. [18] The study also found that out of 100 participants majority 91% of the samples were found to be having normal self esteem 6% of the samples were with low self esteem and only 3% samples having high self esteem. The mean of the self-esteem score among children of mentally ill parents is 20.75± 2.84.…”
Section: Discussionmentioning
confidence: 85%
“…In the tool 10 statements (4, 5, 6, 10, 12,14,15,16, 21 and 24) are negative and rest 18 statements are positive. Scores are classified (0-9) as low psychological well being, (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) as intermediate psychological well being and (21-28) as high psychological well being. Higher the score, higher the psychological well being.…”
Section: Methods/approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship disturbance was marked by disorganized attachment so that her children had difficulty trusting others. Herbert, Manjula, and Philip (2013) stated that the relationship disturbance of the children who live with schizophrenic parents caused them to have emotional, social, and academic difficulty. The emotional difficulties felt by those children were fear, loneliness, and the loss of peace and happiness in the family.…”
Section: Introductionmentioning
confidence: 99%